Geotectônica e evolução crustal das faixas Rio Preto e Riacho do Pontal, estados da Bahia, Pernambuco e Piauí - Fabricio de Andrade Caxito (2013)
The Rio Preto and Riacho do Pontal fold belts are part of the extensive Brasiliano / Pan- African branch of orogens of West Gondwana in Northeast Brazil, extending up to 600 km in a SWNE trend within the northwest and north São Francisco Craton margins. The Rio Preto Fold Belt is composed by Formosa Formation (schist, quartzite, amphibolite), probably deposited in a paleoproterozoic (~1.9 Ga) back-arc basin and thus part of the basement to the fold belt; and the Canabravinha Formation (metadiamictite, metawacke, metaturbidite), probably deposited in a Neoproterozoic (900-600 Ma) rift basin. Neoproterozoic deformation originated a complex assymetrical doubly-vergent fan structure, between 600 and 540 Ma ago. The Rio Preto Fold Belt probably represents the inversion of an intracontinental basin, as orogenic or oceanic rocks have not yet been identified within its outcropping area. The Riacho do Pontal Fold Belt can be subdivided in three tectono-stratigraphic domains, from north to south: The Internal (metamorphic core), Central (ophiolitic) and External (thrust-and-fold belt) zones. The Internal Zone contains important Tonianaged (1000-960 Ma) augen-gneiss intrusions (Afeição Suite) which might represent a continuation of the Cariris Velhos Orogen further northeast. The Central Zone, whose geophysical characteristics are very similar to those of Precambrian suture zones, is characterized by the Monte Orebe Complex, composed mainly by metabasalts and deep-sea metasedimentary rocks. Sm-Nd whole rock data suggest extrusion of the metabasalt protholits at around 820 Ma. Initial Nd(t) = +4.4 and 147Sm/144Nd values above the chondrite ratio indicates a depleted mantle source, which together with a T-MORB, subduction-related ophiolite geochemistry, suggest that the metabasalts represent obducted remnants of a Neoproterozoic oceanic crust. The External Zone is characterized by the Casa Nova nappe system, which is composed by two units, from the bottom up: The Barra Bonita Formation, representing a platformal sequence which is broadly coeval to the cratonic cover of the Una Group and thus represent part of the northern São Francisco paleocontinent passive margin; and the Mandacaru Formation, which is a turbiditic, flysch-like unit, deposited in an active margin basin with sources toward north, at around 630 Ma ago. The whole belt is intruded by extensive syn to post- collisional granitoids of late Neoproterozoic to Cambrian age (~630-530 Ma). The Riacho do Pontal Fold Belt probably represents a complete plate tectonics cycle in the late Neoproterozoic, involving the collision of the São Francisco Craton with the western edge of the Pernambuco Alagoas block further north. This interpretation challenges a view of the Borborema Province as a coherent block since the Paleoproterozoic (part of the Atlantica Supercontinent); suggesting, instead, a dynamic setting where multiple plates interacted to form this portion of West Gondwana.